APLIKASI BERBAGAI JENIS ZAT PENGATUR TUMBUH (ZPT) TERHADAP PERTUMBUHAN SEMAI GAHARU (Aquilaria malaccensis Lamk.) - Aisyah, Siti; Arlita, Tuti; ', M. Mardhiansyah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Aquilaria malaccensis Lamk. in trade name of the wood product (incense) results by few of tree species that resulting agarwood. In few of international tend, this product known as agarwood, aloeswood or oudh. Cultivation of Aquilaria malaccensis Lamk. is the most important thing to did for conserve this type. Agarwood is Not Wood of Forest Product (NWFP) that has high economic value so plants of agarwood should be expanded, but in Aquilaria malaccensis Lamk.  plants cultivation not easy to did, therefore for the growing must gived treatment by giving PGR, so that plant grows be better. Therefore need to know better types of PGR for growth of Aquilaria malaccensis Lamk.  at  seedling stage by different PGR giving. The aims of research is knowing Aquilaria malaccensis Lamk.  seedling by various types of plant growth regulator. This research used Completely Randomize Design (CRD) consisting of 4 treatments with 3 repetitions, for each respective unit consist of 10 seedling, so total of all experiment unit is 120. Observation data analyzed by variance analyze if showed real effect or very real effect to be continued by the Smallest Real Test (SRL) 5%. Plant Growth Regulator (PGR) giving Rootone F with 750 ppm concentration results better tend to improve quality of Aquilaria malaccensis Lamk.  seedling in terms of survival percent 76,66%, high seedling added 3,06 cm, diameter seedling added 0,28 mm. Keywords : PGR, Growth, Aquilaria malaccensis Lamk. Seedling